After egg collection, can we predict the chance of embryos for day 5 transfer or freezing?. Issue 3 (4th October 2021) - Robertson, I; Chmiel, F P; Cheong, Y
Abstract : Lay summary: Even partway through an IVF cycle, at the point when a woman's eggs have been collected, it is hard to provide reliable answers to the common question of 'Am I likely to have a good embryo to transfer?' Sometimes, it only takes one good egg to be successful. However, doctors and patients are acutely aware that low egg numbers, older age and having conditions such as endometriosis can stack the odds against success. We have developed a model to try and answer this question for those patients who wish for more information to help guide their expectations after egg collection. A new tool is presented to predict whether a woman having IVF treatment will have a good enough embryo either to transfer on day 5 or freeze. It was built using information from all 2015 to 2016 UK cycles and predicts using age, number of eggs collected and cause of subfertility.